2020
DOI: 10.1371/journal.pone.0238792
|View full text |Cite
|
Sign up to set email alerts
|

Association between health insurance membership and anaemia among children under-five years. Evidence from Ghana

Abstract: Introduction Anaemia is prevalent among children in developing countries. The main objective of this study was to assess the association between health insurance membership and anaemia among Ghanaian children under-five years. Methods We obtained Ghana’s Multiple Indicators Cluster Survey, 2011 dataset from the United Nations International Children’s Emergency Fund. Data were analyzed with the aid of Stata/IC, version 15. Results The prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
2
3
0
Order By: Relevance
“…Mothers who are not aware of NHIS coverage on malaria at the health facility are more likely to have their children suffer severe and moderate anaemia compared to those who are aware. Similar findings were reported by previous studies [ 47 49 ]. These studies reported that health insurance coverage serves as a protective factor against childhood anaemia and improves child health outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…Mothers who are not aware of NHIS coverage on malaria at the health facility are more likely to have their children suffer severe and moderate anaemia compared to those who are aware. Similar findings were reported by previous studies [ 47 49 ]. These studies reported that health insurance coverage serves as a protective factor against childhood anaemia and improves child health outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies on the significant association between maternal health insurance coverage and child’s health outcome in Ghana [ 50 , 51 ] and other SSA countries [ 52 ], our findings further showed that the risk of under-five death was significantly lower among the children of mothers who were covered by health insurance and explained the importance of universal access to health insurance schemes in reducing the risks of U-5 M. As observed in previous studies [ 53 , 54 ], this plausibly revealed the negative implications of mothers’ financial constraints in seeking healthcare, especially on their children’s health outcomes. This suggests the need for the expansion of health insurance schemes to every child under the age of 5 years, as well as accrediting health insurance schemes at the primary and private healthcare facilities to ensure the enrolment of disadvantaged people.…”
Section: Discussionsupporting
confidence: 93%
“…Prior studies among the adult population showed that health insurance enrolment was associated with educational status, wealth, age, marital status, gender, type of occupation and place of residence [ 23 25 ]. In addition, an analysis of the 2011 Ghana Multiple Indicator Cluster Survey (MICS) revealed that a majority (73%) of children under five years were non-insured [ 26 ]. However, there is a paucity of literature on determinants of health insurance enrolment among children under five years.…”
Section: Introductionmentioning
confidence: 99%